Cognitive Flexibility, COVID-19-related Anxiety, and the Related Factors in Iranian Nurses: A Cross-sectional Study - Mahsa Rezaei; Mahsa Hosseini; Mahbobeh Sajadi; Azam Muslimi (Iran University of Medical Sciences, 2023)
Background & Aims The spread of COVID-19 pandemic caused anxiety in the medical staff, especially nurses, which contributed to many physical and mental problems in them. The relationship between cognitive flexibility and COVID-19-related anxiety is still unknown. This study aims to measure the relationship between cognitive flexibility and COVID-19-related anxiety in nurses, and find the related factors. Materials & Methods This is a descriptive-analytical study with a cross-sectional design that was conducted in 2021 on 120 male and female nurses working in one of the hospitals affiliated to Arak University of Medical Sciences. Sampling was done using a stratified and random sampling method for three months. The cognitive flexibility inventory (CFI) and the corona disease anxiety scale (CDAS) were employed to collect data. Data analysis was performed in SPSS software, version 23, using independent t-test, analysis of variance (ANOVA) , and Pearson correlation test. Results The mean total score of CDAS was 21.09±3.96, ranged from 12 to 32. The mean total score of CFI was 52.78±9.97, ranged from 30 to 81. Based on Pearson's correlation test results, there was no significant relationship between cognitive flexibility and COVID-19-related anxiety (p>0.05). The mean scores of CFI and CDAS were not significantly different based on age, number of children, work experience, physical activity level, and educational level; however, nurses with permanent employment (P=0.007) and female nurses (P=0.03) had higher cognitive flexibility, and married nurses had lower anxiety (P=0.021). Conclusion There is no significant relationship between cognitive flexibility and COVID-19-related anxiety in nurses. The personality traits such as cognitive flexibility is not enough to reduce the high level of anxiety caused the pandemics such as COVID-19 and it requires multiple measures and strategies.